2021
DOI: 10.1177/10731911211009312
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal and Gender Invariance Analysis of the Strengths and Difficulties Questionnaire Across Ages 3, 5, 7, 11, 14, and 17 in a Large U.K.-Representative Sample

Abstract: Developmental invariance is important for making valid inferences about child development from longitudinal data; however, it is rarely tested. We evaluated developmental and gender invariance for one of the most widely used measures of child mental health: the parent-reported Strengths and Difficulties Questionnaire (SDQ). Using data from the large U.K. population-representative Millennium Cohort Study ( N = 10,207; with data at ages 3, 5, 7, 11, 14, and 17 years), we tested configural, metric, scalar, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 82 publications
7
40
2
Order By: Relevance
“…At age 3, an age‐adapted version of the SDQ was administered. Psychometric analyses of the SDQ have generally been favourable (for a review, see Kersten et al., 2016 ), showing invariance across informants, gender and development (ages 5–14) in the MCS (Murray, Speyer, Hall, Valdebenito, & Hughes, 2021a , 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…At age 3, an age‐adapted version of the SDQ was administered. Psychometric analyses of the SDQ have generally been favourable (for a review, see Kersten et al., 2016 ), showing invariance across informants, gender and development (ages 5–14) in the MCS (Murray, Speyer, Hall, Valdebenito, & Hughes, 2021a , 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the change in emotional and behavioral difficulties over time, linear, rather than quadratic, latent growth models were used since quadratic terms were not statistically significant, with emotional and behavioral difficulties measured at ages 5, 7, 11, and 14 years used as indicators. Emotional and behavioral difficulties measured at 3 and 17 years were not included since only partial scalar invariance was supported (Tables S8 and S9; also see Murray, Speyer, Hall, Valdebenito, & Hughes, 2021). Factor loadings on the latent intercept (the average emotional and behavioral difficulties score at a chosen time point) were fixed to be 1 and the latent slopes (the change rate in emotional and behavioral difficulties from 5 to 14 years) were fixed by the age differences in years between assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric properties the SDQ have been extensively examined (see Kersten et al., 2016 for a review), including in the current sample (Murray et al., 2021a , 2021b ). These studies have mostly confirmed the reliability and validity of its scores (Goodman, 1997 , 2001 ; Goodman, Meltzer, & Bailey, 1998 ).…”
Section: Methodsmentioning
confidence: 99%